Hydrophobic polyvinylidene fluoride membrane modified with silica nanoparticles and silane for succinic acid purification using osmotic distillation process - Jun Ying Tan,; Wei Lun Ang,; Abdul Wahab Mohammad, (Penerbit Universiti Kebangsaan Malaysia, 2021)
Recently, osmotic distillation (OD) has emerged as an alternative process for the concentration and purification of heat sensitive components. However, OD performance was severely affected by membrane fouling and wetting, which could be minimized through membrane surface roughness creation and surface energy modification. This study incorporated silica nanoparticles and coated tridecafluro-1,1,2,2-tetrahydrooctyl-1-triethoxysilane at various concentration onto polyvinylidene fluoride (PVDF) membrane to improve its hydrophobicity, limiting the contact between foulants in feed solution and membrane surfaces. Generally, the addition of silica reduced the water contact angle (WCA) of the membrane, but the inclusion of silane had increased it. These membranes were then tested through OD with 1 wt% succinic acid feed solution and 50 wt% calcium chloride stripping solution. PVDF membranes that have been modified with 1 wt% silica nanoparticles and coated with 1:50 volume ratio silane solution achieved a transmembrane flux of 0.6019 kg/m2 ⋅h, the highest flux among silanated membrane. This was due to the larger pore size retained after silanization. A rejection rate of 95.66% and above were achieved by the membranes fabricated in this study. Overall, PVDF membrane modified with silica and silane had been successfully utilized in OD process and shown potential as a concentration and purification process.